Hemodynamic consequences of severe lactic acidosis in shock states: from bench to bedside. Issue 1 (January 2016) - Kimmoun, Antoine; Novy, Emmanuel; Auchet, Thomas; Ducrocq, Nicolas; Levy, Bruno
Abstract Lactic acidosis is a very common biological issue for shock patients. Experimental data clearly demonstrate that metabolic acidosis, including lactic acidosis, participates in the reduction of cardiac contractility and in the vascular hyporesponsiveness to vasopressors through various mechanisms. However, the contributions of each mechanism responsible for these deleterious effects have not been fully determined and their respective consequences on organ failure are still poorly defined, particularly in humans. Despite some convincing experimental data, no clinical trial has established the level at which pH becomes deleterious for hemodynamics. Consequently, the essential treatment for lactic acidosis in shock patients is to correct the cause. It is unknown, however, whether symptomatic pH correction is beneficial in shock patients. The latest Surviving Sepsis Campaign guidelines recommend against the use of buffer therapy with pH ≥7.15 and issue no recommendation for pH levels <7.15. Furthermore, based on strong experimental and clinical evidence, sodium bicarbonate infusion alone is not recommended for restoring pH. Indeed, bicarbonate induces carbon dioxide generation and hypocalcemia, both cardiovascular depressant factors. This review addresses the principal hemodynamic consequences of shock-associated lactic acidosis. Despite the lack of formal evidence, this review also highlights the various adapted supportive therapy options that could be putatively added to causal treatment in attempting to reverse the hemodynamic consequences of shock-associated lactic acidosis.